Efficiency in Property Formalization: Evaluation of Nullities in Acquisitive Prescription and Notarial Improvement Strategies - Mendoza Vásquez, Enrique (2024)
The 2017 National Census by INEI revealed that 76% of housing in Peru is owned, yet nearly half of these properties lack official titles. To address this, Laws N° 27157 and 27333 enable notaries to formalize property through acquisitive prescription. However, many of these procedures have been annulled by the judiciary due to non-compliance with legal norms. This essay examines common causes of nullity, such as deficiencies in notification and legal requirements, and highlights the need for procedural improvements. Implementing jurisprudence-based recommendations, alongside advanced technologies and continuous training, will enhance legal security and confidence in the notarial system, facilitating the formalization of informal properties and promoting economic development and social cohesion.